2001
DOI: 10.5433/1679-0359.2001v22n1p21
|View full text |Cite
|
Sign up to set email alerts
|

Nematóides Ciatostomíneos (Strongylidea, Strongylidae) em eqüinos criados a pasto no Estado de São Paulo, Brasil

Abstract: By previous fecal examinations, 14 naturally nematode infected equine hosts were selected from horsebreeding farms in Jaboticabal County, São Paulo State, Brazil. The animals were divided in two experimental groups according to age: seven animals, 12 to 24 months old, were allotted to the Young Group and the other seven equines, all of them with more than 60 months old, constituted the Adult Group. One week later all 14 equine hosts were slaughtered and the separate contents, plus a thorough scraping, of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…In autopsy studies reported in different parts of the world, Oxyuris equi has been recorded at a rate of 7-90% (Bucknell et al, 1995;Barbosa et al, 2001;Pereira and Vianna, 2006), and 4.1-17% in stool examinations (Sotiraki et al, 1997;Eslami et al, 2005). In Turkey, Burgu et al (1995) found Oxyuris equi as 30% in their autopsy study, while it was reported to be between 0.6-7.6% in some studies based on stool examinations (Demir et al, 1995;Pişkin et al, 1999;Gül et al, 2003;Bakırcı et al, 2004;Altaş et al, 2005;Uslu and Güçlü, 2007;Umur and Açıcı, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In autopsy studies reported in different parts of the world, Oxyuris equi has been recorded at a rate of 7-90% (Bucknell et al, 1995;Barbosa et al, 2001;Pereira and Vianna, 2006), and 4.1-17% in stool examinations (Sotiraki et al, 1997;Eslami et al, 2005). In Turkey, Burgu et al (1995) found Oxyuris equi as 30% in their autopsy study, while it was reported to be between 0.6-7.6% in some studies based on stool examinations (Demir et al, 1995;Pişkin et al, 1999;Gül et al, 2003;Bakırcı et al, 2004;Altaş et al, 2005;Uslu and Güçlü, 2007;Umur and Açıcı, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Os endoparasitos mais relevantes pertencem às famílias Strongylidae, Trichostrongylidae, Ascarididae e Oxyuridae, com maior destaque patogênico para os grandes estrôngilos (Strongylus vulgaris, S. equinus e S. edentatus), ciatostomíneos (pequenos estrôngilos), Parascaris equorum, Strongyloides westeri, Trichostrongylus axei e Oxyuris equi (MENETRIER et al, 2020). Os ciatostomíneos são os parasitos mais prevalentes e com maior intensidade parasitária em equinos no Brasil, representando de 80-100% da carga parasitária total (BARBOSA et al, 2001;PEREIRA, VIANNA, 2006;MATTOS et al, 2020).…”
Section: ____________________________________________________________...unclassified
“…Strongylus vulgaris, S. equinus and S. edentatus), as well as Parascaris equorum, Oxyuris equi, Strongyloides westeri, Trichostrongylus axei, Habronema spp., Dictyocaulus arnfield and Anoplocephala spp. (Barbosa et al, 2001;Molento, 2005).…”
Section: Introductionmentioning
confidence: 99%